Thermal comfort investigation of multi-storey residential buildings in Mediterranean climate with reference to Darnah, Libya - Elaiab, Fatima M. (2014)
The main aim of this research is to investigate occupants’ thermal comfort and energy performance of multi-storey residential buildings in one of the major cities in Libya (Darnah). The work was implemented in stages as follows: